Long-Term Neuropsychological Outcome in Preterm Twins - Giovanni Iannone; Clelia Tripaldi; Antonino Chindemi; Lorenzo Piscitelli; Antonio Mastrorocco; Silvano Palazzo; Luigi Esposito (The Scientific World Journal)
Few long-term studies have yet described neuropsychological outcome in preterm twins. Our aim was to assess, by long-term evaluation, neuropsychological outcome in preterm twins in order to define a correct follow-up program. Our study was a cohort one, with an index and a comparison group. Neonatal medical records of all preterm newborns admitted to our centre between 1991 and 1997 were reviewed and selected patients were recalled. The sample population included two matched groups of children aged 6—12 years, 86 twins and 86 singletons, submitted to paediatric, neurological, psychological, and ophthalmological examinations. Inclusion criteria were twin pregnancy and gestational age 27—36 weeks for index group; same gestational age, but single pregnancy, for the comparison group. All children underwent paediatric and neuropsychiatric examinations, cognitive assessment, and psychological evaluation by standardized tests for screening of learning specific disorders and language difficulties, and finally, ophthalmological examination. In order to study their role in predicting neuropsychological outcome, we examined some perinatal prognostic factors by statistical analysis. Unfavourable neuropsychological outcome was observed in 55/172 (32%) children, with different prevalence in the two groups, 42/172 (24%) in twins and 13/172 (8%) in singletons. Statistical analysis performed for examined prognostic factors showed significant differences in neuropsychological outcome with regard only to gestational age < 32 weeks, low birth weight, intraventricular haemorrhage, and periventricular leukomalacia. The incidence of neuropsychological diseases in the two groups showed significant difference about language and learning difficulties. Our data suggest that preterm twins represent a particular high-risk category of premature babies, mostly regarding the risk of so-called “minimal brain dysfunction”, so a careful follow-up is recommended.